On the stabilization of a thermoelastic laminated beam system with microtemperature effects - FOUZIA, Foughali; DJELLALI, Fayssal (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
The present article investigates a one-dimensional thermoelastic laminated beam with microtemperature effects. Using the energy method, we prove in the case of zero thermal conductivity that the unique dissipation due to the microtemperatures is strong enough to exponentially stabilize the system if and only if the wave speeds of the system are equal. Our result is new and improves previous results in the literature. Mathematics Subject Classification (2010): 35B40, 74F05, 93D15, 93D20. Received 22 October 2024; Accepted 28 February 2025.